A Comparison of Al-Mawardi and Zakiah Daradjat's Thoughts on the Ideal Educator - Ratna Kasni Yuniendel (TADRIS: Jurnal Pendidikan Islam, 2025)
Education in Indonesia is said to have been unsuccessful (if not a failure) in achieving national educational goals. Among the indications of this is the suboptimal guidance provided by educators to students, especially in the affective domain, highlighting the need to optimize the role and function of educators in formal institutions. The purpose of this study is to analyze and compare the thoughts of Al-Mawardi, a classical scholar, and Zakiah Daradjat, a modern educational psychologist, on the concept of the ideal figure of an educator in formal educational institutions. This research is library research (literature study). The primary data sources for this research consist of the works of Al-Mawardi and Zakiah Daradjat, while the secondary data sources include books and literature related to the two figures being studied. The results of the study show that Al- Mawardi emphasizes the importance of noble character, profound knowledge, and authority as the main characteristics that an educator must have, in line with the Islamic educational perspective that emphasizes morality and leadership. Meanwhile, Zakiah Daradjat emphasizes the psychological aspects of education, focusing on empathy, attention to students' mental health, and the importance of an emotional approach that supports students' holistic development. Although both come from different social contexts, their thoughts complement each other in an effort to shape the ideal educator.